Age-specific incidence of allergic and non-allergic asthma - Pakkasela, Johanna; Ilmarinen, Pinja; Honkamäki, Jasmin; Tuomisto, Leena E.; Andersén, Heidi; Piirilä, Päivi; Hisinger-Mölkänen, Hanna; Sovijärvi, Anssi; Backman, Helena; Lundbäck, Bo; Rönmark, Eva; Kankaanranta, Hannu; et al. (BMC pulmonary medicine, 2020)
Onset of allergic asthma has a strong association with childhood but only a few studies have analyzed incidence of asthma from childhood to late adulthood in relation to allergy. The purpose of the study was to assess age-specific incidence of allergic and non-allergic asthma. Questionnaires were sent to 8000 randomly selected recipients aged 20-69 years in Finland in 2016. The response rate was 52.3% (n = 4173). The questionnaire included questions on e.g. atopic status, asthma and age at asthma diagnosis. Asthma was classified allergic if also a physician-diagnosed allergic rhinitis was reported. The prevalence of physician-diagnosed asthma and allergic rhinitis were 11.2 and 17.8%, respectively. Of the 445 responders with physician-diagnosed asthma, 52% were classified as allergic and 48% as non-allergic. Median ages at diagnosis of allergic and non-allergic asthma were 19 and 35 years, respectively. Among subjects with asthma diagnosis at ages 0-9, 10-19, 20-29, 30-39, 40-49, 50-59 and 60-69 years, 70, 62, 58, 53, 38, 19 and 33%, respectively, were allergic. For non-allergic asthma, the incidence rate was lowest in children and young adults (0.7/1000/year). It increased after middle age and was highest in older age groups (2.4/1000/year in 50-59 years old). The incidence of allergic asthma is highest in early childhood and steadily decreases with advancing age, while the incidence of non-allergic asthma is low until it peaks in late adulthood. After approximately 40 years of age, most of the new cases of asthma are non-allergic.